(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, the author examines the development of civil society in Uzbekistan from the perspective of philosophical analysis and consideration of its historical and philosophical retrospective. Paying attention to the foundations of civil society and its importance for the development of any country, the author shows exactly what factors influence this process, and also deduces its features in Uzbekistan.